Do Children and Adolescents with Overweight or Obesity Adhere to the National Food-Based Dietary Guidelines in Greece? - Alexandra Georgiou; Odysseas Androutsos; Giorgos Chouliaras; Evangelia Charmandari (MDPI AG, 2022)
Childhood obesity increases the risk for metabolic disorders, but is also related to nutritional deficiencies, such as anemia and hypovitaminosis D. Although children/adolescents with overweight/obesity may have higher energy intake, their diet quality and diversity may be low. The present study aimed to evaluate the consumption of foods against the national food-based dietary guidelines in children and adolescents with overweight or obesity in Greece. Sociodemographic, anthropometric and lifestyle data were collected from a sample of 1467 children 2-18 years old (962 obese, 505 overweight, 51.2% females) in 2014-2017. The results of this study show that the consumption of dairy products, fruit, vegetables, legumes and fish by children/adolescents with overweight or obesity was lower than the national recommendations (ranging from a minimum of 39.5% for fish, to a maximum of 75.5% for cereal/potato/rice). Only the consumption of meat/poultry was found to exceed the national recommendation (estimated coverage of 131.3%). Moreover, a large proportion of participants regularly consumed various unhealthy foods/beverages. The present findings indicate that the majority of children/adolescents with overweight/obesity do not comply with the national food-based dietary guidelines in Greece. The implementation of new strategies to promote healthy diets among children/adolescents with overweight/obesity are urgently required.